2014
DOI: 10.1007/s00726-014-1866-0
|View full text |Cite
|
Sign up to set email alerts
|

Leucine is a major regulator of muscle protein synthesis in neonates

Abstract: Approximately 10% of infants born in the United States are of low birth weight. Growth failure during the neonatal period is a common occurrence in low birth weight infants due to their inability to tolerate full feeds, concerns about advancing amino acid supply, and high nutrient requirements for growth. An improved understanding of the nutritional regulation of growth during this critical period of development is vital for the development of strategies to improve lean growth. Past studies with animal models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 86 publications
(141 reference statements)
0
68
0
9
Order By: Relevance
“…Emerging evidence shows that l-leucine has a signaling role in the small intestine to activate the mammalian target of rapamycin (mTOR), thereby stimulating protein synthesis and inhibiting proteolysis (Rhoads and Wu 2009). Similar functions of l-leucine have also been reported for other tissues, including skeletal muscle (Columbus et al 2015;Davis et al 2010;Escobar et al 2006) and mammary gland tissue (Lei et al 2011(Lei et al , 2013. Thus, either dietary supplementation with l-leucine or provision of leucine-rich meal leads to increased protein accretion in tissues (Li et al 2011a;Yin et al 2010).…”
Section: Introductionmentioning
confidence: 78%
“…Emerging evidence shows that l-leucine has a signaling role in the small intestine to activate the mammalian target of rapamycin (mTOR), thereby stimulating protein synthesis and inhibiting proteolysis (Rhoads and Wu 2009). Similar functions of l-leucine have also been reported for other tissues, including skeletal muscle (Columbus et al 2015;Davis et al 2010;Escobar et al 2006) and mammary gland tissue (Lei et al 2011(Lei et al , 2013. Thus, either dietary supplementation with l-leucine or provision of leucine-rich meal leads to increased protein accretion in tissues (Li et al 2011a;Yin et al 2010).…”
Section: Introductionmentioning
confidence: 78%
“…Because continuous feeding is still indicated in some infants when there is meal feeding intolerance, strategies to enhance the efficient use of dietary nutrients administered this way would be beneficial. Previous studies have demonstrated that the stimulatory effect of amino acids can be reproduced largely by leucine (12,75) and that supplementation with leucine, either parenterally or enterally, stimulates protein synthesis, provided that an adequate supply of amino acids is available (33-36, 59, 74, 75, Results are expressed as means Ϯ SE (n ϭ 11-12). rpS4, ribosomal protein S4; rpS8, ribosomal protein S8; ODC, ornithine decarboxylase; P/NP, polysomal/nonpolysomal.…”
Section: Discussionmentioning
confidence: 99%
“…The essential amino acid leucine is a primary regulator of muscle protein synthesis (12,75), as it acts not only as a substrate for protein synthesis but also as a signaling molecule to enhance protein synthesis in muscle (1,15) and other tissues (57). This effect appears to be unique to leucine, as other branched-chain amino acids do not have this effect (35).…”
mentioning
confidence: 99%
“…Supplementation with the branched-chain amino acid leucine also enhances protein synthesis during the neonatal period (14,29). Leucine is an important substrate for protein synthesis, but it also functions as a signaling molecule to enhance muscle protein synthesis (4,15) through activation of the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway (3,28,29).…”
mentioning
confidence: 99%